A multi-timescale modeling methodology for PEMFC performance and durability in a virtual fuel cell car. (14th December 2015) - Mayur, Manik; Strahl, Stephan; Husar, Attila; Bessler, Wolfgang G.
Abstract: The durability of polymer electrolyte membrane fuel cells (PEMFC) is governed by a nonlinear coupling between system demand, component behavior, and physicochemical degradation mechanisms, occurring on timescales from the sub-second to the thousand-hour. We present a simulation methodology for assessing performance and durability of a PEMFC under automotive driving cycles. The simulation framework consists of (a) a fuel cell car model converting velocity to cell power demand, (b) a 2D multiphysics cell model, (c) a flexible degradation library template that can accommodate physically-based component-wise degradation mechanisms, and (d) a time-upscaling methodology for extrapolating degradation during a representative load cycle to multiple cycles. The computational framework describes three different time scales, (1) sub-second timescale of electrochemistry, (2) minute-timescale of driving cycles, and (3) thousand-hour-timescale of cell ageing. We demonstrate an exemplary PEMFC durability analysis due to membrane degradation under a highly transient loading of the New European Driving Cycle (NEDC). Highlights: A flexible simulation framework for PEMFCs spanning over multiple timescales. A time-upscaling approach to predict cell end-of life under automotive driving cycle. Introduction of degradation library for flexible durability analysis.